Intrinsic and extrinsic contributors to the cardiac benefits of exercise - Hastings, Margaret H.; Castro, Claire; Freeman, Rebecca; Abdul Kadir, Azrul; Lerchenmüller, Carolin; Li, Haobo; Rhee, James; Roh, Jason D.; Roh, Kangsan; Singh, Anand P.; Wu, Chao; Xia, Peng; et al. (JACC Basic to translational science, 2024)
Among its many cardiovascular benefits, exercise training improves heart function and protects the heart against age-related decline, pathological stress, and injury. Here, we focus on cardiac benefits with an emphasis on more recent updates to our understanding. While the cardiomyocyte continues to play a central role as both a target and effector of exercise’s benefits, there is a growing recognition of the important roles of other, noncardiomyocyte lineages and pathways, including some that lie outside the heart itself. We review what is known about mediators of exercise’s benefits—both those intrinsic to the heart (at the level of cardiomyocytes, fibroblasts, or vascular cells) and those that are systemic (including metabolism, inflammation, the microbiome, and aging)—highlighting what is known about the molecular mechanisms responsible.